Wide-Bandgap Double Perovskites with Multiple Longitudinal-Optical Phonon Scattering - Wang, Liangling; Zheng, Wei; Vitale, Francesco; Zhang, Xiangzhou; Li, Xiuling; Ji, Yanchen; Liu, Zhen; Ghaebi, Omid; Plass, Christian T.; Domes, Robert; Frosch, Torsten; Soavi, Giancarlo; et al. (Advanced Functional Materials, 2022)
Alloyed lead-free double perovskites display intense photoluminescence, are environmentally friendly, and their devices show long-term operation. Thanks to these properties, which make them excellent warm white-emitting materials, they have recently received great attention in lighting applications. An important factor to tune the optical properties of alloyed lead-free double perovskites is the presence of self-trapped excitons. Here, it is demonstrated that in lead-free double perovskites, the strong electron–phonon coupling plays a crucial role in the generation of self-trapped excitons. The strong electron–phonon coupling is confirmed by a large Huang–Rhys factor and by the presence of multiphonon transitions. In particular, sharp emission lines superimposed on the broad photoluminescence emission band of one of these samples (Cs2Ag0.6Na0.4InCl6 0.5%Bi) are observed; these are due to the strong coupling of longitudinal-optical phonons with excited electronic states caused by the tetragonally distorted AgCl6 octahedrons. Such a strong coupling of longitudinal-optical phonons to electrons can effectively modulate the photophysical properties of alloyed double perovskites, and its understanding is, thus, of paramount importance for the design of future optoelectronic devices.
CRIS-Team Scopus Importer:2023-04-20
Keywords: electron–phonon coupling; lead-free double perovskites; multiphonon transitions; resonant Raman spectroscopy; self-trapped excitons